Planet of the apes (2001) [videorecording (DVD)] - Wahlberg, Mark, 1971-; Roth, Tim; Bonham Carter, Helena, 1966-; Duncan, Michael Clarke; Kristofferson, Kris; Warren, Estella; Giamatti, Paul; Boulle, Pierre, 1912-1994 (Twentieth Century Fox Home Entertainment, 2002)
In a remake of the original 1968 film, after an astronaut crash-lands on an uncharted planet, he finds himself at odds with a society in which apes are the rulers and humans are little more than slaves.